2021
DOI: 10.3390/diagnostics11020308
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Percutaneous Ablation in the Management of Colorectal Cancer Liver Metastatic Disease

Abstract: Approximately 50% of colorectal cancer patients will develop metastases during the course of the disease. Local or locoregional therapies for the treatment of liver metastases are used in the management of oligometastatic colorectal liver disease, especially in nonsurgical candidates. Thermal ablation (TA) is recommended in the treatment of limited liver metastases as free-standing therapy or in combination with surgery as long as all visible disease can be eradicated. Percutaneous TA has been proven as a safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 62 publications
(120 reference statements)
0
13
0
Order By: Relevance
“…It is frequently combined with perioperative chemotherapy since this reduces recurrence rates [ 41 ]. Local ablative treatment (LAT) is an acceptable alternative therapy, sometimes the only possible treatment, for patients who are poor candidates for surgery and for patients with post-metastasectomy recurrence [ 3 , 42 , 43 , 44 , 45 , 46 ], the main inclusion criteria for LAT only strategy in the RAXO study. It is also often combined with metastasectomy to obtain a radical procedure when surgery cannot leave a sufficient amount of normal liver behind [ 42 ], constituting the majority of patients with LAT in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is frequently combined with perioperative chemotherapy since this reduces recurrence rates [ 41 ]. Local ablative treatment (LAT) is an acceptable alternative therapy, sometimes the only possible treatment, for patients who are poor candidates for surgery and for patients with post-metastasectomy recurrence [ 3 , 42 , 43 , 44 , 45 , 46 ], the main inclusion criteria for LAT only strategy in the RAXO study. It is also often combined with metastasectomy to obtain a radical procedure when surgery cannot leave a sufficient amount of normal liver behind [ 42 ], constituting the majority of patients with LAT in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The CLOCC trial compared systemic therapy with or without radiofrequency ablation and demonstrated that adding a local treatment might prolong OS in patients with non-resectable CRC liver metastases [ 48 ]; contrary to the aim of cure with LAT in this study. Currently, there is no clear evidence supporting the superiority of one LAT technique over the other [ 43 ]. In oligometastatic mCRC, LAT of lung or liver metastases offers both disease-free and chemotherapy-free intervals [ 3 ] with a favourable safety profile [ 43 , 44 , 45 , 46 ], which may contribute to better QoL compared with systemic therapy only [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiofrequency ablation (RFA) is the most clinically verified and used ablation modality, although it has specific limitations. Alternate energy-based technologies using thermal (hot or cold) effect for focal tumor ablation have been recently introduced in clinical use, namely microwave ablation (MWA), cryoablation (CrA), high-intensity focused ultrasound (HIFU), laser therapy, and irreversible electroporation (IRE) [ 4 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Percutaneous ablation of primary and secondary liver lesions constitutes a well-established therapeutic technique for the management of hepatocellular carcinoma or hepatic metastases of various neoplasmatic origin [ 1 , 2 , 3 ]. Almost all diagnostic methods have been used either solely or in combination (with or without fusion imaging) for ablation guidance [ 4 ]. In the vast majority of ablation sessions, a conventional manual free-hand approach is performed; more recently, however, a stereotactic computer-assisted navigation has been applied, aiming to improve the precision of the needle placement [ 5 , 6 , 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%